The Investigate of Green Open Space Recreation Facilities Based on Homo Urbanicus Theory - Sugiama, Aceng Gima; Firdanti, Khairina Hafsa; Rusmalinda, Sinta Rusmalinda (Politeknik Negeri Bandung, 2024)
This study aims to evaluate visitors' assessments of urban green open spaces based on the Homo Urbanicus theory, encompassing the dimensions of people, opportunity, event, and space. Using data from 178 respondents visiting green open spaces (GOS) in Bandung, the analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that both male and female visitors generally perceive the provision of primary and supporting facilities in GOS similarly. They equally recognize these facilities as essential without distinguishing between genders. However, concerning comfort, perceptions of primary and supporting facilities differ based on gender. Therefore, park management should design primary and supporting facilities to function generically for both men and women while differentiating comfort elements based on gender-specific preferences.